Analisis Bantuan Luar Negeri India Sebagai Emerging Donor Terhadap Krisis Ekonomi di Sri Lanka - Sri Wahyuni, Gusti Ayu (Department of International Relations, Brawijaya University, 2024)
ABSTRACT Sri Lanka was hit by the worst economic crisis in its history, especially since gaining independence in 1948. The economic crisis reached the point where Sri Lanka declared itself unable to pay its debts or was in default. India, as a neighboring country and emerging donor, has emerged to help Sri Lanka restore its economy. India is providing foreign assistance totaling USD 5 billion in 2022 to Sri Lanka. This research aims to analyze India's interests in providing foreign assistance to recover from the Sri Lankan economic crisis using the concept of national interest explained by Nuechterlein. Nuechterlein's concept of national interests consists of four interests, namely economic interests, defense interests, ideological interests, and world order interests. This research uses a qualitative approach whose explanation is descriptive with secondary data obtained through library study techniques. Based on the analysis carried out, of the four interests, there are three interests that are the most prominent and behind India's allocation of foreign aid to the Sri Lankan economic crisis, namely economic interests, defense interests and world order interests Keywords: Economic Crisis, Sri Lanka, India. Foreign Aid ABSTRAK Sri Lanka dilanda krisis ekonomi terburuk sepanjang sejarah mereka terutama sejak memperoleh kemerdekaan pada tahun 1948 silam. Krisis ekonomi tersebut sampai pada titik yang membuat Sri Lanka menyatakan diri tidak mampu membayar utang atau mengalami default. India sebagai negara tetangga sekaligus emerging donor muncul membantu Sri Lanka memulihkan perekonomiannya. India memberikan bantuan luar negeri dengan total mencapai USD 5 miliar pada tahun 2022 kepada Sri Lanka. Penelitian ini hadir dengan tujuan untuk menganalisis kepentingan India dalam memberikan bantuan luar negeri terhadap pemulihan krisis ekonomi Sri Lanka dengan menggunakan konsep kepentingan nasional yang dipaparkan oleh Nuechterlein. Konsep kepentingan nasional Nuechterlein terdiri dari empat kepentingan, yakni economy interest, defense interest, ideology interest, dan world order interest. Penelitian ini menggunakan pendekatan kualitatif yang penjelasannya bersifat deskriptif dengan data-data sekunder yang diperoleh melalui teknik studi pustaka. Berdasarkan analisis yang dilakukan, dari empat kepentingan, terdapat tiga kepentingan yang paling menonjol dan melatarbelakangi alokasi bantuan luar negeri India kepada krisis ekonomi Sri Lanka, yakni economy interest, defense interest, serta world order interest. Kata Kunci: Krisis Ekonomi, Sri Lanka, India, Bantuan Luar Negeri